2008
DOI: 10.1152/japplphysiol.01019.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of airways constriction on exhaled nitric oxide

Abstract: While airway constriction has been shown to affect exhaled nitric oxide (NO), the mechanisms and location of constricted airways most likely to affect exhaled NO remain obscure. We studied the effects of histamine-induced airway constriction and ventilation heterogeneity on exhaled NO at 50 ml/s (Fe(NO,50)) and combined this with model simulations of Fe(NO,50) changes due to constriction of airways at various depths of the lung model. In 20 normal subjects, histamine induced a 26 +/- 15(SD)% Fe(NO,50) decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 21 publications
5
39
0
Order By: Relevance
“…C A NO is normally low and close to zero because of its fast reaction rate with haemoglobin. It may be increased due to increased alveolar dead space and with increased axial diffusion of NO into the alveoli due to bronchoconstriction (31). A reduced FE NO and C A NO are associated with primary pulmonary hypertension (12).…”
Section: Introductionmentioning
confidence: 99%
“…C A NO is normally low and close to zero because of its fast reaction rate with haemoglobin. It may be increased due to increased alveolar dead space and with increased axial diffusion of NO into the alveoli due to bronchoconstriction (31). A reduced FE NO and C A NO are associated with primary pulmonary hypertension (12).…”
Section: Introductionmentioning
confidence: 99%
“…The current American Thoracic Society/European Respiratory Society guidelines recommend measuring the exhaled concentration at a single constant flow of 50 ml/s (i.e., FE NO,50 ), a remarkably simple protocol, and thus easily translatable to the clinic, but may be limiting the potential to utilize exhaled NO as an inflammatory marker. While we understand that exhaled NO is predominantly from the airways at this flow, Verbanck and colleagues (24) suggest that we might more precisely locate the airway source of NO with an accurate mathematical model. Similarly, Kerckx and colleagues (10) use the same model to enhance our understanding of how to accurately determine the small, but potentially important, alveolar concentration.…”
mentioning
confidence: 99%
“…We recently quantified this potential effect and presented a simple method to account for axial diffusion of NO on the estimation of the alveolar concentration (4); however, we only tested the model in healthy subjects. Two new studies (10,24) are presented in the Journal of Applied Physiology, both of which elegantly combine experimental measurements and a mathematical model of NO exchange that advance our knowledge and understanding of NO gas exchange and thus our interpretation of the exhaled NO signal.Kerckx and colleagues (10) have independently developed a similar method to account for axial diffusion of NO into the …”
mentioning
confidence: 99%
“…Other studies using multiple breath nitrogen washout and imaging [32] have shown an increase in ventilation heterogeneity in individuals with hyper reactivity to methacholine which appeared to be independent of changes in airway resistance [33]. Modelling studies indicate that the most marked effect of airways constriction on FeNO50 is most likely to occur in generations 10-15 and that constriction in smaller airways is likely to increase FeNO50 due to interference with the NO back diffusion effect [34]. Ventilation heterogeneity has been reported as a major predictor of airway reactivity independently of the degree of inflammation [35], while airway smooth muscle contraction may be the major cause of airway reactivity [36].…”
Section: Discussionmentioning
confidence: 93%